Effect of heat treatment on phase composition and microstructure of samples of fe-mo-c - Заславський, О.М.; Веліканова, Т.А. (Proceedings of National Aviation University (archive), 2007)
The Fe–Mo–C ternary alloys have been heat-treated by Pirani-Alterthum method. The heat-treatment influence on the changing of phase composition and microstructure of this alloys has been examined by means X-Ray and metallography methods. It was determined that heat-treatment not results in formation of Mn-like π and χ phases in the subsolidus area of the Fe-Mo-C ternary system. Assumption has been put forward that formation of this phases occurs on nonsolid-phase mechanism.